Kajian Intertekstual Mitos Watugunung Dan Legenda Sangkuriang - Pradnya Paramitha, Ni Made Ayu Susanthi (Jayapangus Press, 2021)
Oral literature is literature that includes the literary expressions of citizens in a culture that is spread and passed down orally or by word of mouth. Stories that are included in oral literature are said to be owned by the people because it is not known who the author is. Oral literature is not concerned with facts and truth, but has an important function in people's lives and is believed to exist because in the story it is closely related to the development of everyday life. Armed with deep values, oral literature also has a function as social control. The various incidents presented should play an important role in setting an example for the community to maintain and at the same time limit everything related to moral values. But nowadays, oral literature is often just an ordinary imaginary story. The important messages in the folklore are sometimes not conveyed in their entirety. For this reason, through an intertextual study, this research will reveal the deep messages conveyed in oral literature that is popular in the community. The stories chosen are the myth of Watugunung and the legend of Sangkuriang. The myth of Watugunung that developed in Bali and the famous legend of Sangkuriang in West Java have a similar storyline. By revealing the relationship between the two, it is hoped that this research can provide insight into the deep messages that the ancestors wanted to convey through the cultural heritage of oral literature. In addition, by taking similar stories from two different areas, this research is also expected to provide awareness that basically these moral values apply to society in general. This research is a qualitative research using literature study and comparative method. From the analysis carried out, there is a relationship between the intrinsic elements between the two. While the moral values presented by the two stories are never giving up, prohibiting incest, and being willing to sacrifice.